PREDICTORS AND OUTCOMES OF ACUTE KIDNEY INJURY ASSOCIATED WITH COLISTIN - Ahmad, Bilal; Arshad, Abdul Rehman; Naseem, Arshad; Rasheed, Abdul; Saleem, Zulqarnain; Sabir, Sohail (Journal of Ayub Medical College Abbottabad, 2024)
Background: Colistin is a nephrotoxic drug. We aimed to determine factors predictive of acute kidney injury amongst patients on colistin and study its impact on mortality. Methods: This observational study was done on adult patients receiving colistin in intensive care unit. Exclusion criteria included use of colistin before shifting to intensive care unit, presence of acute kidney injury before starting colistin or unwillingness. Complete blood counts, serum creatinine, albumin, C-reactive protein and lactate were checked at admission. Renal function tests were repeated daily and urine output was regularly monitored. Sequential Organ Failure Assessment score was calculated after 24 hours of admission. Primary outcome was development of acute kidney injury based on KDIGO criteria. Results: There were 150 patients aged 45.17±13.24 years, with a median length of stay of 12 (10–15) days. Mortality rate in intensive care unit was 39.33% (59 patients). Acute kidney injury developed in 78 (52.00%) patients after a mean of 4.26±1.48 days. Serum C-reactive protein (OR=1.011; 95% confidence interval 1.000, 1.023) and lactate (OR=1.714; 95% confidence interval 1.015, 2.895) levels at admission were predictive of acute kidney injury. Serum C-reactive protein ≥92 mg/dl and lactate ≥2.15 mg/dl had sensitivity of 64.10% and 76.92% respectively, and specificity of 75.00% each for predicting acute kidney injury. Patients with AKI were 3.324 (95% confidence interval 1.660,6.656) times more likely to die. Conclusion: Acute kidney injury associated with colistin is a significant problem, and is predicted by serum C-reactive protein and lactate levels at admission.